STATUS KESUBURAN TANAH PADA LAHAN PASANG SURUT DI DESA PUSAKA KECAMATAN TEBAS KABUPATEN SAMBAS - Fauzi, Fatur Rahman (Jurnal Solum, 2023)
This study aims to determine the status of soil fertility and provide fertilization suggestions based on soil fertility status in four types of overflow in Pusaka Village, Tebas District, Sambas Regency. The method used in this research is a survey method. The research starts from November 18 2022 to December 5 2022 and until the presentation of the results. For each location, 5 sampling points were determined outside the reef and 5 sampling points outside the reef. The distance is 100 m between the 4 sample points at a depth of 0-30 cm. Composite soil samples are from 5 points on the citrus reef and outside the oranges so that the total number of soil samples taken is 8 samples. The results of the study showed Assessment of soil fertility status in Pusaka Village, Tebas District, Sambas Regency has low criteria. The available P nutrients in the soil at the study site were very high, so there was no need to apply P fertilization. The recommendations for fertilizing urea and KCl at the study site were A =171,52 kg/ha dan 295,73 kg/ha, lokasi B = 179,33 kg/ha dan 1.318,17 kg/ha, lokasi C = 168,72 kg/ha dan 215,67 kg/ha, lokasi D = 156,8 kg/ha